2023
DOI: 10.1002/minf.202300006
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐aided design of muscarinic acetylcholine receptor M3 inhibitors: Promising compounds among trifluoromethyl containing hexahydropyrimidinones/thiones

Abstract: The new high selective mAChRs M3 inhibitors with IC50 in nanomolecular ranges, which can be the prototypes for effective COPD and asthma treatment drugs, were discovered with computational approaches among trifluoromethyl containing hexahydropyrimidinones/thiones. Compounds [6‐(4‐ethoxy‐3‐methoxy‐phenyl)‐4‐hydroxy‐2‐thioxo‐4‐(trifluoromethyl)hexahydropyrimidin‐5‐yl]‐phenyl‐methanone (THPT‐1) and 5‐benzoyl‐6‐(3,4‐dimethoxyphenyl)‐4‐hydroxy‐4‐(trifluoromethyl)hexahydropyrimidin‐2‐one (THPO‐4) have been proved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For pharmacological testing in vitro on multicellular smooth muscle preparations of rat tracheal rings, seven most promising compoundsamides of 1-oxo-3-phenyl-isochroman-6carboxylic acid (1-7, Table 1) with predicted cholinolytic activity were selected through preliminary in silico screening. As a target for screening, the spatial structure of the M3 type cholinergic receptor, reconstructed in our previous studies [19], were used. Structure of these compounds are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For pharmacological testing in vitro on multicellular smooth muscle preparations of rat tracheal rings, seven most promising compoundsamides of 1-oxo-3-phenyl-isochroman-6carboxylic acid (1-7, Table 1) with predicted cholinolytic activity were selected through preliminary in silico screening. As a target for screening, the spatial structure of the M3 type cholinergic receptor, reconstructed in our previous studies [19], were used. Structure of these compounds are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Using a phospholipase C inhibitor (U-73122) and blockers of inositol 1,4,5-trisphosphate-sensitive (2-APB) and ryanodine-sensitive (caffeine) Ca 2+ channels of the sarcoplasmic reticulum, it was demonstrated that the aforementioned compounds act on the intracellular signaling cascade through M3 type muscarinic cholinergic receptors [28][29][30][31]. Previously, we established [19] that for the known non-selective competitive antagonist of muscarinic cholinergic receptors, ipratropium bromide, the slope of the Schild regression line was 0.79 ± 0.07 (coefficient of determination R 2 = 0.99), and the affinity value pKB was 9.14 ± 0.62 with an IC50 of 7.24•10 -10 M. Therefore, compound 7 has a lower affinity and is characterized by higher EC50 values compared to ipratropium bromide. However, a critically important advantage of compound 7 is its ability, at equal concentrations, to more effectively inhibit signal transmission through M3 cholinergic receptors compared to ipratropium bromide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation